Abdominal fibrosarcoma in an eight-month-old infant - Benedetti, Juan Luis; Pittamiglio, Horacio; del Carmen Gutiérrez, Maria; Pérez Scremini, Alberto; Giguens, Washington; Lorenzo, Julio; Chavarría, Oscar (Cirugía del Uruguay, 1986)
We report a case of lnfantile Fibrosarcoma located in the retroperitoneum of an 8 month old child who presented with a rapidly growing abdominal mass. The interest of the case rests on the rarity of this tumor-, specially in this location. The place of surgery, radiotherapy and chemotherapy are discussed.